2023
DOI: 10.3390/s23198196
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Analysis of Deep Learning Convolutional Neural Network Architectures for Fault Diagnosis of Broken Rotor Bars in Induction Motors

Kevin Barrera-Llanga,
Jordi Burriel-Valencia,
Ángel Sapena-Bañó
et al.

Abstract: Induction machines (IMs) play a critical role in various industrial processes but are susceptible to degenerative failures, such as broken rotor bars. Effective diagnostic techniques are essential in addressing these issues. In this study, we propose the utilization of convolutional neural networks (CNNs) for detection of broken rotor bars. To accomplish this, we generated a dataset comprising current samples versus angular position using finite element method magnetics (FEMM) software for a squirrel-cage roto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…However, after careful evaluation, ResNet-152 was chosen as it exhibited the best performance. Its deeper architecture and skip connections enable it to capture intricate patterns and features in the data effectively [84]. Therefore, ResNet-152 was selected for the proposed method and subsequently fine-tuned for the ALL dataset.…”
Section: G Classifiermentioning
confidence: 99%
“…However, after careful evaluation, ResNet-152 was chosen as it exhibited the best performance. Its deeper architecture and skip connections enable it to capture intricate patterns and features in the data effectively [84]. Therefore, ResNet-152 was selected for the proposed method and subsequently fine-tuned for the ALL dataset.…”
Section: G Classifiermentioning
confidence: 99%
“…Eduardo and colleagues successfully employed a frequency occurrence plot-based CNN (FOP-CNN) to diagnose motor faults using solely the motor current signature. Kevin et al [16] evaluated the diagnostic capabilities of six different CNN architectures and found that VGG19 performed the best in diagnosing broken bar faults during rotor operation in induction motors. Rahmawan et al [17] utilized CNN to detect misalignment of motor shafts.…”
Section: Stage 2: Improved Cnn For Motor Fault Diagnosismentioning
confidence: 99%
“…Meanwhile, in [15], the authors presents an in-tegrated design strategy focusing on preserving closed-loop functionality while leveraging active fault diagnostic and tracking control to detect early flaws. Authors in [16] advocate for the utilization of zonotopic observers and MANFIS models to ensure reliable detection of broken rotor bars (BRBs). However, [17] highlights a challenge where the fracture of two bars, situated a pole pitch apart, conceals the fault harmonics, rendering fault detection seemingly impossible.…”
Section: Introductionmentioning
confidence: 99%